PENGARUH KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU DI SEKOLAH MENENGAH ATAS NEGERI 6 KOTA CIREBON - Asep Kurniawan (IAIN Syekh Nurjati Cirebon, 2019)
The purpose of this study was to determine the extent of the influence of principal’s leadership on the teachers’ performance in Senior High School 6 Cirebon. The variables are the principal’s leadership (X) and teachers’ performance (Y). The sample consisted of 15 teachers and 34 students. The instruments are questionnaires and documentation. The data analysis technique was inferential analysis techniques with simple regression. Based on inferential statistical calculations of hypothesis testing, the value of t or Ha = 3.412 was greater than the value obtained from the distribution table t table or Ho = 1.684 with a significant level of 5% (Ha≥ Ho) = (3,412 ≥1,684). This research proved that the A hypothesis was accepted, O hypothesis was rejected. It means that the principal’s leadership the influences the teachers’ performance in Senior High School 6 Cirebon City. Keywords: competence, responsibility, structure, managerial